A Tailor-Made Metropolitan Union. Is This a Good Solution of the Metropolitan Governance Problem in Poland? - Kaczmarek, Tomasz (Frontiers in Sustainable Cities, 2021)
The scale and dynamics of socio-economic and spatial processes in Poland in the last three decades, including territorial diversification of the pace of economic development and demographic and social changes, as well as processes such as metropolisation and suburbanization, determine new challenges in the management and programming of the development of large cities and their areas functional. The new processes require state and local authorities to take actions in the strictly political, legal and organizational and planning dimensions. In Poland, for almost 20 years, there has been a discussion on the introduction of specific forms of management of metropolitan areas. Failure to adopt systemic solutions at the level of the entire country (lack of political will for metropolitan reform and the creation of metropolitan self-government county) leads to the emergence of numerous grassroots integration initiatives of local governments (metropolitan associations of cities and municipalities). Since 2015, the EU cohesion policy instrument Integrated Territorial Investments has been implemented in functional urban areas. Since 2017, the first multi-task metropolitan union (Metropolitan Union of Upper Silesia—Górnoślasko-Zagłebiowska Metropolis) established by the parliament (special act) and the government (executive regulation) has been operating in Poland. The first—sui generis—statutory metropolis encourages local authorities of other metropolitan areas to adopt their own legislative initiatives (Kraków, Łódz, Tricity: Gdańsk-Gdynia-Sopot). Is the choice of the path for creating individual statutory solutions for each of the Polish metropolises in the form of a metropolitan union appropriate? Does diferrentia specifica for various metropolitan areas seem to be the most justified at the moment, taking into account the political conditions and the bottom-up and top-down approach to metropolitan governance in Poland? The article presents the complex path to solving the issue of management in Polish metropolitan areas and assesses the legitimacy of a solution based on a model tailored to each metropolis, introduced by a separate metropolitan act.